c.2 - Association of Indian Universities (New Delhi, 1985)
Question Bank is that unique bank which makes available to teachers and examining bo dies a large number of questions together with associated Information they might wish to use in preparing tests and examinations during or at the end of a course. It is a collection of questions put together by experts. The differences in its various concepts generally lie in terms of the number of questions which may constitute a bank, their level of refinement. the detalls of item analysis, data carried with the questions as also in the functions assign ed to the bank. Opinions differ as to the number of questions which go to make a question bank but there is no denying the fact that it is a major component of examination reform to help produce better quality Items and questions that are valid. reliable and appropriate to the abilities to be tested; a revolt against the ste reotyped, repetitive and memory-based questions normally asked In the examinations. It is by no means an attempt to short circuit the process of learning but. In fact, a device to regulate and quicken the of learning. Indeed, to be able to ask the right kind of questions requires a thorough understanding of the subject matter; and to participate in the task of setting questions is itself an educative process. The process of producing questions/items for a question bank might very well result in a clarification of the aims and objectives of examinations. This could lead to the specification of subject objectives In fairly precise and behavioural terms. But this does not mean that a question bank would consist solely of those questions in which the course objectives can be accurately defined and measured. A question bank could dearly be composed of all kinds of questions now being used for internal and external assessment ranging from the 'open' or 'es say type' to the 'dosed' or 'objective type Item'. It is necessary that a question bank must contain a large number of questions/ Items on a particular subject.
Keywords: Law